The Concept of Building System of Balanced Indicators in Business-Planning of Fuel and Power Complex - T. B. Temukuev (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Current conditions of making business require more flexibility and adaptability of companies to changes in external environment. Due to this fact traditional methods of business-planning based only on finance indicators are becoming insufficient to ensure long-term success of organization. The author substantiated a choice of key trends in assessing the company work at the fuel and power complex in order to raise efficiency of business-planning. A balanced system of indicators was proposed, which meets the principles of process management by goals and provides opportunity to trace compliance of process results to strategic goals of organization and cascade steps of the system to subsidiary and affiliate companies and divisions. The concept relies on building the strategic map, where key indicators are divided into five separate groups: finance indices, customer indicators, factors of in-business processes, training and development of personnel and relatively new point, i. e. power-efficiency and sustainable development.